Immunocytochemical study of BCR and bcr-abl localization in K562 cells - Telegeev, G.D.; Dubrovska, A.N.; Nadgorna, V.A.; Dybkov, M.V.; Zavelevich, M.P.; Maliuta, S.S.; Gluzman, D.F. (Experimental Oncology, 2010)
Aim: To obtain polyclonal antibodies against recombinant proteins recognizing Bcr domain and fusion region of Bcr-Abl and analyze the patterns of intracellular distribution of Bcr and Bcr-Abl proteins in K562 cells of chronic myelogenous leukemia. Methods: The coding sequences of DН and РН domains of Bcr-Abl were cloned, and the recombinant proteins were expressed in E. coli. The rabbit polyclonal antibodies were produced and used for immunocytochemical study of Bcr and Bcr-Abl localization in K562 cells. Results: The gene constructs containing sequences coding for DН and РН domains of Bcr-Abl have been obtained. The antibodies with relative specificity to corresponding recombinant proteins differ by the patterns of their intracellular reactivity with Bcr- and Bcr-Abl related structures. While Bcr protein is located predominantly perinuclearly, antibody against hybrid Bcr-Abl protein is reacted with the structures in cell periphery, namely on cell membranes. Conclusion: Antibodies against DН and РН domains of Bcr-Abl react with proteins located differently in chronic myelogenous leukemia cells. The difference in intracellular localization of Bcr and Bcr-Abl may be attributable to the different domains interacting with different multiprotein complexes.